THE INFLUENCE OF COMPETENCE AND JOB ANALYSIS ON PERFORMANCE WITH CAREER AS AN INTERVENING VARIABLE AT THE OFFICE OF EDUCATION AND CULTURE MEDAN CITY - Seriyanti. S; Kiki Farida Ferine; Yohny Anwar (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Competence and Job Analysis on Employee Performance with Career as a mediating variable at the Office of Education and Culture of Medan City. The research method used is a quantitative approach with data collection techniques through the distribution of questionnaires to a number of employees as respondents. Data analysis was performed using Partial Least Square (PLS) through the SmartPLS 3.0 application to test validity, reliability, and relationships between variables in the research model. The results show that Competence has a positive and significant effect on Career and Employee Performance. Job Analysis also has a positive and significant effect on Career and Employee Performance. Furthermore, Career is proven to have a positive and significant effect on Employee Performance. However, the mediation test results show that Career does not significantly mediate the effect of Job Analysis on Performance, while Career significantly mediates the effect of Competence on Employee Performance. Therefore, it can be concluded that improving employee competence and implementing effective job analysis play an important role in enhancing employee performance, with career development becoming a significant intermediary factor in the relationship between competence and performance at the Office of Education and Culture of Medan City.